Barrier Properties of Cr/Ta-Coated Zr-1Nb Alloy under High-Temperature Oxidation - Syrtanov M. S. Maksim Sergeevich; Korneev S. P. Stepan Pavlovich; Kashkarov E. B. Egor Borisovich; Sidelev D. V. Dmitry Vladimirovich; Moskvichev E. N. Evgeny Nikolaevich; Kudiyarov V. N. Victor Nikolaevich (2024, 2024)
In this paper, Cr (8 μm)/Ta (3 μm) bilayer coatings deposited on a Zr-1Nb alloy substrate were investigated and compared with a Cr-coated alloy under high-temperature steam oxidation at 1200–1400 °C. The bilayer coatings with α- and β-Ta interlayers were obtained by magnetron sputtering. The Cr/Ta-coated samples were studied using scanning electron microscopy (SEM), X-ray diffraction (XRD), and optical microscopy (OM). The coating with an α-Ta interlayer can suppress the interdiffusion of chromium and zirconium more effectively up to 1330 °C in comparison with the coating having a β-Ta interlayer. The weight gain of the α-Ta-coated samples after oxidation at 1200 °C for 2000 s was 5–6 times lower than that of the Cr-coated Zr alloy samples. Oxidation at 1400 °C for 120 s showed no significant difference in the weight gain of the Cr- and Cr/Ta-coated Zr-1Nb alloy samples. It was shown that the effect of suppression of Zr-Cr interdiffusion by the barrier coating (α- and β-Ta) is only short-term.